Hellas Mon Amour: Revisiting Greece's national sites of trauma (E. Solomon (ed.), Contested Antiquity. Archaeological Heritage and Social Conflict in Modern Greece and Cyprus, 2021)
If “the past is a foreign country”, then Greece’s classical past could be described – and it has been – as an ideal, as well as idyllic land, colonized by the West. This paper employs post-colonial theory combined with discussions of trauma as a historical agent in order to investigate ways in which contemporary Greek museums and archaeological sites strive to attract the colonial gaze by reclaiming ownership of the nation’s (neo)-classical past; at the same time, however, this exercise may be seen as an effort to alleviate the pains of modernity as experienced by a people who has never overcome the trauma of its separation from its famed antiquity. As a result, Greek archaeological spaces – both museums and sites – can be described as “sites of trauma”, as the placescapes where the unlived experiences of an imagined past become revived. A number of examples are discussed, including the Benaki and Acropolis Museums, as well as several clusters of antiquities preserved “in situ”, mostly within the urban grid or incorporated in buildings and other structures, such as Athenian metro stations. Such cases of incidental archaeology, the paper contends, are devised in order to suture, in the psychoanalytical sense of the term, Greek national imaginary onto the very sites where the nation experienced the trauma of its separation from its past.